PROXIMATE AND PHYTOCHEMICAL COMPOSITION AND ANTIOXIDANT PROPERTIES OF INDIGENOUS LANDRACES OF OMANI FENUGREEK SEEDS - Ali, Amanat; Waly, Mostafa I; Bhatt, Neeru; Al-Saady, Nadiya A (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Fenugreek (Trigonella foenum graecum L) is receiving global attention as a functional food due to its unique nutritional and medicinal properties as anti-diabetic, hypocholesterolemic, antipyretic, anti-carcinogenic and seasoning and flavoring agent.Materials and Methods: Seeds of indigenous fenugreek accessions were collected from three different ecological regions (Al-Dakhaliyah, Al¬Dhahirah, and Al-Batinah) of Sultanate of Oman. The samples were analyzed for proximate chemical composition, phytochemical contents and antioxidant properties.Results: Only significant (P<0.05) differences were observed in the crude fiber and gross energy values of fenugreek seeds collected from different regions of Oman. The highest crude fiber content (8.6 %) was observed in samples collected from Al-Dhahirah region whereas the lowest value (7.1%) was found in samples collected from Al-Dakhaliyah region. No significant (P<0.05) differences were however observed in the moisture, crude protein, crude fat, and ash contents of samples collected from the three regions of Oman. The regional variability significantly (P<0.05) affected the phytochemicals composition and the highest amount of total phenolics (139.2 mg GAE/100g) were recorded in samples collected from Al-Batinah, followed by Al-Dhakhliyah (130.0 mg GAE/100g) and Al-Dhahirah (127.8 mg GAE/100g) regions, respectively. A significant correlation was also observed between the total phenolic contents and the antioxidant properties of fenugreek seeds as determined by reducing power potential (FRAP).Conclusion: Indigenous landraces of Omani fenugreek seeds are a rich source of protein, dietary fiber, and many important bioactive components, which were found to be significantly correlated with its antioxidant properties.